Effect of Health Education on Maternal Behaviors and Pediatric Burn Prevention - Azam Geravandi; Shahnaz Maleki (Mazandaran University of Medical Sciences, 2019)
Background: One of the important indicators of development and health in countries is the mortality rate of children under the age of 5 years. In recent years, the mortality rate has dropped below the age of 5, but is still higher in developing countries. The purpose of this study was to evaluate the effect of health education on changes in maternal behavior and pediatric burn prevention.  Methods: This interventional study was conducted on mothers of children aged <5 years referred to the health centers in Kermanshah, Iran. The questionnaire was provided in two steps before and two months after the training. The educational program was presented via group discussion, question and answer sessions and educational pamphlets. Data analysis was performed in SPSS software using paired t-test. Results: The educational programs had a significant effect on the behavior of mothers. Before intervention, 16% of mothers were hugging their babies while having hot drinks, which dropped to 6% after intervention and also resulted in 13% reduction in the use of unheated tools. Moreover, 15% of children had access to fireworks before teaching their mothers, which dropped to 6% after intervention. Conclusions: It is suggested that providing interventional measures such as health education for parents, especially mothers, can be an effective way for pediatric burn prevention.